Intracranial otogenic complications in adults: new factors that influenced its onset, frequency and nature - Małgorzata Wierzbicka; Michalina Staśkiewicz; Oskar Rosiak; Katarzyna Karmelita-Katulska; Witold Szyfter; Wojciech Gawęcki (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background To compare the clinical features of two time cohorts of patients: “pre-COVID-19” and “COVID-19”—admitted as emergency with intracranial otogenic complications, with special regard to sigmoid sinus thrombosis (CVST). Methods Retrospective analysis of patients documentation concerning urgent procedures of intracranial otogenic complications at tertiary-referral otolaryngology department. Analysed database—pre-COVID-19 cohort (January–February 2019/2020): 1434 otological outpatient visits, 509 planned otosurgeries and 17 urgent otological procedures; COVID-19 cohort (March–April 2020/2021): 1150, 566 and 20 respectively. Overall intracranial complications: 5 and 9 respectively. Analysed outcome measures: incidence proportion of otogenic intracranial complications in relation to planned and urgent otosurgical procedures; incidence proportion of intracranial complications in relation to the total number of emergency and planned outpatient consultations and the total number of planned surgical procedures. Results There were 14 intracranial complications, 5 in the pre-COVID and 9 in the COVID cohort, including 1 and 5 sigmoid sinus thrombosis, respectively. Out of them, 3 and 5 patients reported a prior history of chronic otitis media, respectively. In COVID period, CVST was more prevalent, with 2 cases (22.2%) presenting solitary CVST, and 3 cases (33.3%) CVST and a simultaneous brain abscess or meningitis. CVST was much more frequent in the COVID period (p < 0.01). Conclusions Despite the published data which suggest that CVST is a rare event associated with COVID-19 infection, based on our experience, CVST can be expected as a frequent component of intracranial otogenic complications during COVID-19 pandemic time. Trial registration This research study was conducted retrospectively from data obtained for clinical purposes. We consulted extensively with the Bioethics Committee at Poznan University of Medical Sciences who determined that our study did not need ethical approval. An official waiver of ethical approval was granted from the Bioethics Committee at Poznan University of Medical Sciences. Graphical abstract